Green river rising - Willocks, Tim (New York : Avon, 1995)
Serving a sentence at Green River Prison, Dr. Ray Klein works in the AIDS-infested prison infirmary, while forensic psychologist Juliette Devlin conducts research on the criminal mind and a mentally challenged man waits for a sign from God. Reprint. NYT.
Keywords: Prison riots -- Texas -- Fiction; Prisoners -- Texas -- Fiction; Prisons -- Texas -- Fiction; Fiction; Adventure fiction